sta4321-3

# sta4321-3 - If AB = , then P ( A B ) = P ( A ) + P ( B ) ....

This preview shows pages 1–4. Sign up to view the full content.

§2.4 Counting Rules Useful in Probability

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
From Last Time Algebraic Laws Let S be a sample space and A , B , C be three events in S . Cumulative Law A B = B A AB = BA Associative Law ( A B ) C = A ( B C ) ( AB ) C = A ( BC ) Distributive Law A ( B C )= AB AC A ( BC )=( A B )( A C ) De Morgan’s Laws ± n i = 1 A i = ² n i = 1 A i ² n i = 1 A i = ± n i = 1 A i Arthur Berg §2.4 Counting Rules Useful in Probability 2/ 4
From Last Time Defnition o± a Probability Defnition (probability) A probability is a mapping o± events to the real numbers such that the ±ollowing three conditions hold: (i) P ( A ) 0 ±or any event A ; (ii) P ( S )= 1 where S is the sample space; (iii) A 1 , A 2 , . . . are mutually exclusive (meaning A i A j = ±or any i ± = j ) then P ± ² i = 1 A i ³ = ´ i = 1 P ( A i ) . Arthur Berg §2.4 Counting Rules Use±ul in Probability 3/ 4

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
From Last Time Implications of conditions (i)-(iii) (a) P ( )= 0. (b)
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: If AB = , then P ( A B ) = P ( A ) + P ( B ) . (c) For any events A and B , P ( A B ) = P ( A ) + P ( B )-P ( AB ) . (d) If A B , then P ( A ) P ( B ) . (e) For any event A , 0 P ( A ) 1. (f) P ( A ) = 1-P ( A ) (g) Principle of Inclusion-Exclusion Theorem (Principle of Inclusion-Exclusion) Given events E 1 , . . . , E n , P ( n i = 1 E i ) = n i = 1 P ( E i )- i 1 &lt; i 2 P ( E i 1 E i 2 ) + + (-1 ) r + 1 i 1 &lt; i 2 &lt; ir P ( E i 1 E i 2 E ir ) + + (-1 ) n + 1 P ( E 1 E n ) Arthur Berg 2.4 Counting Rules Useful in Probability 4/ 4...
View Full Document

## This note was uploaded on 10/04/2011 for the course STA 4321 taught by Professor Staff during the Fall '08 term at University of Florida.

### Page1 / 4

sta4321-3 - If AB = , then P ( A B ) = P ( A ) + P ( B ) ....

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online